Tangled roots : social and psychological factors in the genesis of terrorism - Victoroff, Jeffrey Ivan (NATO security through science series. Human and societal dynamics ;, 2006)
What do we really know about the contributing causes of terrorism? Are all forms of terrorism created equal, or are there important differences in terrorisms that one must know about to customize effective counter-strategies? Does poverty cause terrorism? This book talks about the basic human ingredients that combust to produce violent extremism.